2023
DOI: 10.1093/biolre/ioad005
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of growth differentiation factor 9 blocks folliculogenesis in pigs

Abstract: Growth differentiation factor 9 (GDF9) is a secreted protein belonging to the transforming growth factor (TGF)-beta superfamily and has been well characterized for its role during folliculogenesis in the ovary. Although previous studies in mice and sheep have shown that mutations in GDF9 disrupt follicular progression, the exact role of GDF9 in pigs has yet to be elucidated. The objective of this study was to understand the role of GDF9 in ovarian function by rapidly generating GDF9 knockout (GDF9−/−) pigs by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Knockout of GDF9 and BMP15 impairs mammalian follicle and oocyte development and reduces ovulation and fertilization rates. 57,58 In contrast, increased GDF9 and BMP15 expression appears to contribute to follicular development and granulosa cell proliferation, increasing the ovulation number and the oocyte fertilization rate. 59–63 Furthermore, our in vitro data demonstrated that the addition of 1 mM and 2 mM methionine enhanced follicle diameter increase.…”
Section: Discussionmentioning
confidence: 99%
“…Knockout of GDF9 and BMP15 impairs mammalian follicle and oocyte development and reduces ovulation and fertilization rates. 57,58 In contrast, increased GDF9 and BMP15 expression appears to contribute to follicular development and granulosa cell proliferation, increasing the ovulation number and the oocyte fertilization rate. 59–63 Furthermore, our in vitro data demonstrated that the addition of 1 mM and 2 mM methionine enhanced follicle diameter increase.…”
Section: Discussionmentioning
confidence: 99%
“…In females, several ubiquitously expressed genes were targeted in the oocyte using the conditional deletion approach, leading to dramatic phenotypes, including: a significant alteration of the reserve of primordial follicles (Pten [25]) or the loss of oocytes with an early arrest of follicular growth (Omcg1 [26]; Mdm2 [27]). Several other genes highly or exclusively expressed in the oocyte were invalidated by a global knock-out approach, leading to different phenotypes, like: sterility with a blockage of follicular growth at the primary stage (Gdf9 in the mouse [28] and in the pig [29]), sterility with a significant defect of oocyte maturation (Patl2 [30]), or sterility with an arrest of early embryonic development (e.g., maternal genes Nlrp5, Stella, Nmp2, and Zar1 [31]).…”
Section: Introductionmentioning
confidence: 99%